2016
DOI: 10.18240/ijo.2016.10.24
|View full text |Cite
|
Sign up to set email alerts
|

Decreased paraoxonase1 activity and increased malondialdehyde and oxidative DNA damage levels in primary open angle glaucoma

Abstract: To investigate the malondialdehyde (MDA) levels, paraoxonase1 (PON1) activity and 8-hydroxy 2-deoxyguanosine (8-OHdG) levels in the primary open angle glaucoma (POAG) patient. Blood samples from 52 healthy individuals and 53 patients with POAG were analyzed for MDA and 8-OHdG by HPLC (high-performance liquid chromatography) and PON1 by spectrophotometry. The data obtained were analyzed statistically. MDA levels were 10.46±8.4 and 4.70±1.79 µmol; PON1 levels were 121±39.55 and 161.62±60.22 U/mL; and 8-OHdG valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…To date, there has been increasing evidence to suggest that an imbalance in the oxidative stress system may be involved in the pathogenesis of glaucoma. Several studies have investigated the level of oxidative stress-related markers in the aqueous humor [ 7 , 22 ] and peripheral blood [ 9 , 23 , 24 ] of patients with glaucoma, as well as the expression of oxidative stress-related markers in humans [ 25 , 26 ] and an experimental glaucoma model's ocular tissues [ 27 ]. Engin et al [ 28 ] reported that the serum levels of TAS, SOD, and GPX decreased and serum levels of MDA increased in patients with glaucoma, which provides compelling evidence for imbalance in the oxidative stress system in the peripheral blood of glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there has been increasing evidence to suggest that an imbalance in the oxidative stress system may be involved in the pathogenesis of glaucoma. Several studies have investigated the level of oxidative stress-related markers in the aqueous humor [ 7 , 22 ] and peripheral blood [ 9 , 23 , 24 ] of patients with glaucoma, as well as the expression of oxidative stress-related markers in humans [ 25 , 26 ] and an experimental glaucoma model's ocular tissues [ 27 ]. Engin et al [ 28 ] reported that the serum levels of TAS, SOD, and GPX decreased and serum levels of MDA increased in patients with glaucoma, which provides compelling evidence for imbalance in the oxidative stress system in the peripheral blood of glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…Using the initial search strategy, we identified 482 articles, and 460 articles were excluded. A total of 22 studies [19, 23–43] were included in this meta-analysis. Detailed characteristics of each included study are presented in Tables 1 –4.…”
Section: Resultsmentioning
confidence: 99%
“…An increased intraocular pressure is a high risk factor of POAG, but normal intraocular pressure can also lead to optic nerve damage and loss of vision in POAG [45]. Although the causes of OAG are unknown, oxidative stress appears to play a role in progressive glaucomatous optic nerve damage [23, 30, 36]. The blood TAS in the meta-analysis of OAG patients decreased, which suggested a breakdown of the balance between the ROS generation and clearance systems.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, content of MDA and NO in retinal tissue of ultrasound group was lower than that of NGF group and Rg1 group, and the content of SOD was higher than that of NGF group and Rg1 group, and the differences were statistically significant, indicating that the use of ultrasound microbubbles can achieve targeted drug administration to increase the drug concentration in eyes. So, ginsenoside Rg1 and NGF mediated by ultrasound targeted microbubble destruction is effective in the treatment of glaucomatous optic nerve damage, which may be related to the changed contents of NO, MDA and SOD ( 16 18 ). This study provided references for the studies on mechanism of the role of oxidative stress injury in the occurrence and development of glaucoma.…”
Section: Discussionmentioning
confidence: 99%